Hollow S-nitrosothiols nanoparticle with polymeric brushes for nitric oxide (NO)-releasing as tumor targeted chemotherapy. Issue 2 (22nd January 2019) - Wang, Jilan; Bi, Ye; Ruan, Hongyan; Sun, Guoqing; Cui, Xianping; Yang, Xinlin; Qin, Chengkun
Abstract: A kind of tumor targeting nitric oxide donor nanoparticle with brushes is described in this paper. The poly(4-vinylphenylboronic acid) polymeric brush, which shows glucose and pH dual responsiveness, endows the ability of hollow S -nitrosothiols nanoparticle to accurate recognition and binding with the sialic acid over-expressed type tumor cells, such as HepG2 and MCF-7 cells. In vitro experiments, including cells capture and release experiments, confocal fluorescence microscope characterization, cytotoxicity assay with different cells, demonstrate the selective recognition and the controlled NO release to kill tumor cells for these S -nitrosothiols nanoparticles. Low concentration of the released NO from the S -nitrosothiols nanoparticles in the transmission would participate physiological activity and avoid serious side effects because the endogenous nature and the physiological necessity to regulate normal biological functions. To the best of our knowledge, this is the first report about polymer nanoparticles as NO donors with functional brushes to selectively identify tumor cells and release NO in a controlled manner.